CONTROL OF UNIFIED POWER QUALITY CONDITIONER UNDER GRID VOLTAGE SAG AND NONLINEAR LOADS - Nguyen Thi Thanh Truc; Van Tan Luong; Huynh Nhat Quang (HUIT Journal of Science, 2024)
In this paper, a control scheme based on feedback linearization (FL) control technique with or without resonant control for unified power quality conditioner (UPQC) which is known as series active filter and shunt active filter, is proposed to compensate both the load voltages and grid currents under grid voltage sags and nonlinear loads. A nonlinear model of system consisting of series active filter and shunt active filter in the dq synchronous reference frames is derived. The load voltage based on FL with resonant control and grid current controllers based on only FL in dq components are designed, depending on series and shunt active filters, respectively. With the proposed scheme, the load voltages are regulated to reach the rated value and both waveforms of load voltages and grid currents are controlled to become almost sinusoidal, compared with the proportional-integral (PI) controller. Simulation results are given to prove the effectiveness of the proposed method.